Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.

Persönlichkeit, Prokrastination und Prüfungsangst als Prädiktoren für Studienerfolg. Wer tritt am Semesterende zur Prüfung an? - Freudinger, Markus (Die Hochschullehre)

Künstliche Intelligenz fachfremd mittels Open Educational Resources unterrichten. Wie das Flipped-Classroom-Format bei der Einbettung in die Lehre der Anglistik hilft. - Mindt, Ilka (Künstliche Intelligenz mit offenen Lernangeboten an Hochschulen lehren. Erfahrungen und Erkenntnisse aus dem Fellowship-Programm des KI-Campus.)

Introduction: English Linguistics, Learners and the Classroom - Hahn, Charlotte Anna; Mindt, Ilka (Anglistik)
Keywords: General Medicine

"There". Die Verwendung von "there" im authentischen Englisch, im Englisch von Lernenden und in Schulbüchern - Mindt, Ilka (Sprachwissenschaft und Fremdsprachendidaktik: Konstruktionen und Konstruktionslernen)

Student engagement in digitalen Lehr-Lern-Szenarien - Mindt, Ilka; Rebekka, Schmidt (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre.)

Student engagement in digitalen Lehr-Lern-Szenarien - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)
In diesem Beitrag wird das Konzept des student engagement mit den drei Dimensionen Verhalten, Emotion und Kognition skizziert und in Bezug auf die unterstützenden Faktoren für Lehre auf Distanz in digitalen Lehr-Lernsettings untersucht. Ein Abgleich der theoretischen Grundlagen mit Forschungsergebnissen verschiedener Studien zum Onlinesemester 2020 sowie eine Konkretisierung durch Evaluationen aus Seminaren der englischen Sprachwissenschaft und der Kunstdidaktik gibt Aufschluss darüber, wie ein geeignetes how to engage auch in digitalen Lehr-Lernsettings gelingen kann. Darüber hinaus lassen die Ausführungen erkennen, dass die unterstützenden Faktoren häufig in ähnlich priorisiert werden. Daraus ergibt sich eine Reihenfolge mit dem unterstützenden Umfeld an erster, aktivem und kollaborativem Lernen an zweiter, Erleben von Kompetenz an dritter und akademischer Herausforderung an vierter Stelle. Die Ergebnisse können damit einen Weg aufzeigen, wie auch in ungewohnten Lehr-Lernsettings sukzessive ein geeignetes how to engage entwickelt werden kann, um student engagement zu fördern.

Einleitung - Meister, Dorothee; Mindt, Ilka (Mobile Medien im Schulkontext)

Mit digitalen Arbeitsformen das Lernen bereichern: zur Gestaltung sinnstiftender Präsenzphasen mit dem Inverted-Classroom-Modell - Mindt, Ilka; Schmidt, Rebekka; Beißwenger, Michael; Dietrich, Nico (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Bridging - Fremdsprache und Fachwissenschaft. Digital Learning Map - Mindt, Ilka

"Digital Humanitites: The Role of the Digital in English Philology". Sprachwissenschaftliche Sektion beim Anglistentag 2017 in Regensburg - Mindt, Ilka; Bartsch, Sabine (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka (Paderborner Unireden 148)

Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Section I: Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka

Welcome back to school: Aussprache in Klasse 5 prüfen - Bredenbröcker, Martina; Hahn, Charlotte Anna (Englisch 5 - 10)
Keywords: Abschlussprüfung Englisch; Auslautverhärtung; Aussprache; awareness raising activities; final-obstruent devoicing; Lautschulung; oral exam; pronunciation; silent letters; th; w vs. v

Proceedings of the BHQFHE projects. Basis, Analysis, Development, Impact and Prosepcts of the BHQFHE Tempus Project

Chosen - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik)

Analyzing Corpus Data from Within - Mindt, Ilka (Anglistik. International Journal of English Studies)

Accreditation of Study Programs - Mindt, Ilka (Proceedings of the BHQFHE projects. Basis, Analysis, Development, Impact and Prosepcts of the BHQFHE Tempus Project)

Chosen - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik)

Shoulda, Coulda, Woulda – Non-Canonical Forms on the Move? - Freudinger, Markus (Zeitschrift für Anglistik und Amerikanistik)
Abstract In this paper, the contractions shoulda, coulda, woulda are compared with their respective full forms should have , would have , and could have . Although the full forms are used much more frequently and are, therefore, considered canonical, the non-canonical forms have increased in frequency throughout the better part of the twentieth century. They are predominantly used in American English – in conversation as well as in fictional writing to imitate speech. With respect to their syntactic environment, shoulda, coulda , and woulda behave differently than their full counterparts since they are often used without subjects and without lexical verbs. Some of these uses can be explained by the fact that shoulda, coulda , and woulda are not always used as verbal items but also as nouns, adjectives, and interjections. Due to their overall low frequency and their restriction to a particular register, however, it appears they will keep their non-canonical status for the foreseeable future.
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics

On the Kinda Peripheral Character of Gotta and what we Oughta Do about it - Freudinger, Markus (Exploring the Periphery)

40 issues of ICAME News/ICAME Journal - Mindt, Ilka (ICAME Journal 40)

An interview with Joybrato Mukherjee, the Chair oft he ICAME Board - Kytö, Merja; Stenström, Anna-Brita; Mindt, Ilka (ICAME Journal 40)

The diachronic development of 'COME TO V' - Mindt, Ilka (Silesian Studies in English 2015)

Anglistentag 2015 Paderborn: Proceedings

Gesprochene Korpora des Englischen und ihre Anwendung in der Grammatikforschung - Mindt, Ilka (Grundlagen einer sprachwissenschaftlichen Quellenkunde)

Syntactic perspectives on directive speech acts : a contrastive study - Freudinger, Markus
This thesis is situated in the field of contrastive pragmatics and compares the syntactic realizations of equivalent directive speech acts in English and German. The term directive speech act is being used in a more narrow sense than intended by Searle (1975).Dramatic plays are used as data source for the original language and the translation into the other language. The four texts are Brechts “Mutter Courage und Ihre Kinder“, Dürrenmatts „Die Physiker“, Osbornes „Look Back in Anger“, and Leighs „Abigail‘s Party“.The central questions of this study are: Which forms are available in each language? Which specific function does a form fulfill in the system of each language? How do forms correspond across languages?In general, realizations as regular sentences, irregular sentences and non-sentences are possible. In the case of regular sentences, the subcategories imperative, declarative, yes-no interrogative, and wh-interrogative are possible in both languages. German also offers the adhortative and the infinitive. There are remarkable differences in terms of frequencies for these types.In general, German and English behave rather similar in their use of the clause types. The detailed qualitative description of specific examples constitutes the main part of the analysis and answers the following questions: which forms occur as equivalences? Under which conditions can declaratives and interrogatives be used directively?Non-sentences also play an important role. Formal categories, however, are not helpful; hence the utterances were grouped according to functional aspects. These are: propositional content, relationship between speaker and hearer, and illocutionary force.

Talking like a book. Investigating colloquialization as a change in written English - Mindt, Ilka (Oralité(s) et écriture(s))

Change in Contemporary English. A Grammatical Study - Mindt, Ilka; Leech, Geoffrey; Hundt, Marianne; Mair, Christian; Smith, Nicholas (Archiv für das Studium der neueren Sprachen und Literaturen 164: 249: 2)

Adjective complementation by that-clauses: An empirical study - Mindt, Ilka

Corpus Linguistics and the Description of English - Mindt, Ilka; Lindquist, Hans (ICAME Journal 35)

Anglistische Korpuslinguistik. Eine Einführung. Grundlagen der Anglistik und Amerikanistik 33 - Mindt, Ilka; Mukherjee, Joybrato (Anglistik. International Journal of English Studies, 22, 1)

Beiträge der Sektion I "'Spoken' English through the Centuries." Sprachwissenschaftliche Sektion beim Anglistentag 2009 in Klagenfurt. - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Spoken English through the centuries: Introduction - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Methoden der Korpuslinguistik: Der korpus-basierte und der korpus-geleitete Ansatz - Mindt, Ilka (Kompendium Korpuslinguistik. Eine Bestandsaufnahme aus deutsch-tschechischer Perspektive)

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Appropriateness in Discourse: The adjectives surprised and surprising in monologue and dialogue - Mindt, Ilka (Journal of Pragmatics)

Adjective complementation by that-clauses: the relation between the semantics of adjectives and the verb phrase in the that-clause - Mindt, Ilka (Anglistik. International Journal of English Studies)

Progressives, Patterns, Pedagogy. A corpus-driven approach to English progressive forms, functions, contexts and diadactic - Mindt, Ilka; Römer, Ute (Anglistik. International Journal of English Studies, 19, 2)

Corpus Linguistics 25 Years on. (Language and Computers: Studies in Practical Linguistics 62) - Mindt, Ilka; Facchinetti, Roberta (ICAME Journal, Computers in English Linguistics, 2008)

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Distributional data and grammatical structures: The case of so- called subject extraposition - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik 54.2, Special issue on "The scope and Limits of Corpus Linguistics – Empiricism in the Description and Analysis of English)

Learner English: Ein Überblick über vorhandene Korpora und mögliche Forschungsansätze - Mindt, Ilka (Korpuslinguistik Deutsch: synchron – diachron – kontrastiv. Würzburger Kolloquium 2003)

Corpora in Applied Linguistics - Mindt, Ilka; Hunston, Susan (ICAME Journal 29, Computers in English Linguistics)

A Student's Introduction to English Grammar - Mindt, Ilka; Huddleston, Rodney; Pullum, Geoffrey K. (Zeitschrift für Anglistik und Amerikanisitk. A Quarterly of Language, Literature and Culture. Heft 2, 2)

Lexikalische Dynamik: Kognitiv-linguistische Untersuchungen am englischen Computerwortschatz - Mindt, Ilka; Bründl, Monika Elisabeth (Anglistik. Mitteilungen des Deutschen Anglistenverbandes)

Is I think a Discourse Marker - Mindt, Ilka (Anglistentag 2002 Bayreuth. Proceedings of the Conference of the German Association of University Teachers of English, Volume XXIV)

Tagungsbericht über das Internationale Kolloquium Korpuslinguistik Deutsch: synchron – diachron – kontrastiv (klde 2003) - Mindt, Ilka (Zeitschrift für Deutsche Philologie 122)

Form and function of parasyntactic presentation structures. A corpus-based study of talk units in spoken English - Mindt, Ilka; Mukherjee, Joybrato (ICAME Journal, 27, Computers in English Linguistics)

Functions of intonation in sentences and texts - Mindt, Ilka (New Frontiers of Corpus Research. Papers from the Twenty First International Conference on English Language Research on Computerized Corpora)

Emerging English Modals: A Corpus-Based Study of Grammaticalization - Mindt, Ilka; Krug, Manfred (Journal of English Linguistics, Volume 30, Number 3)

Intonation im Lancaster/IBM Spoken English Corpus. Falls und fall-rises, Sprecherwechsel, paratones, declination - Mindt, Ilka

Longman Idioms Dictionary - Mindt, Ilka (Anglistik. Mitteilungen des Deutschen Anglistenverbandes)

New Zealand English Grammar Fact or Fiction? A corpus-based study in morphosyntactic variation - Mindt, Ilka; Hundt, Marianne (Anglistik: Mitteilungen des Deutschen Anglistenverbandes)

Prosodic Cues at Speaker Turns - Mindt, Ilka (Corpus Linguistics and Linguistic Theory. Papers from the Twentieth International Conference on English Language Research on Computerized Corpora (ICAME 20))